Pre-service teachers’ perception of service-learning instructional strategy in social studies curriculum in South west Nigeria (2014)
Nigeria at centenary is riddled with poverty and high illiteracy rate, corruption and corresponding increase in unemployment, ineffective governance and apathy on the part of the citizens among others. As a result of these situations, there seems to be a paradigm shift to envisioning many new approaches to educational system to bridge the gap between the school and community for civic engagement. Some of such new approaches may be captured in service–learning instructional strategy (hands-on teaching and learning strategies that integrate meaningful service and classroom content). Indeed, Nigeria is yet to incorporate the service learning into the academic curriculum, despite its’ effectiveness. This paper, therefore investigated pre-service teachers’ perception of service learning in social studies curriculum. A descriptive quantitative survey method was adopted by using random sampling technique to select three public Universities in South-West, Nigeria. Three hundred (300) Social Studies education students were purposively selected, employing Service-Learning Perception Scale (SLPS). The scale was validated and its reliability coefficient was 0.75 using Cronbach Alpha. The data collected were analysed using percentage and t-test Analysis. The findings revealed that students showed greater willingness to enroll for a course in service-learning, if it would improve their career development, promote their personal and social development among others. Based on these findings, policy recommendations were made such as integration of service learning into university curriculum and clear standard guides that are back up by relevant laws should be put in place for proper implementation for civic engagement.